Interleukin-10 Is a Promising Marker for Immune-Related Adverse Events in Patients With Non-Small Cell Lung Cancer Receiving Immunotherapy - Wang, Haowei; Zhou, Fei; Zhao, Chao; Cheng, Lei; Zhou, Caicun; Qiao, Meng; Li, Xuefei; Chen, Xiaoxia (Frontiers in Immunology, 2022)
Abstract Background: Immune checkpoint inhibitors (ICIs) brought about a major paradigm shift in non-small cell lung cancer (NSCLC) treatment. However, the use of ICIs is associated with an unpredictable pattern of immune-related adverse events (irAEs). Therefore, biomarkers to predict occurrence of irAEs are required to avoid overtreatment of ICIs and minimize irAEs development. The purpose of this study was to identify clinical features and plasma inflammatory factors capable of predicting irAEs. Methods: A total of 67 patients who received ICI monotherapy or ICI-based combination therapy were retrospectively identified. Clinical characteristics and plasma inflammatory cytokines were collected and analyzed to screen potential biological markers associated with irAEs. Chi-Square Test and Mann-Whitney U Test were used for the primary analysis. Receiver operating characteristic (ROC) curve was used to determine the optimal cutoff value. Univariate and multivariate logistic regression models were used for identifying risk factors of irAEs. Univariate and multivariate Cox proportional hazards were also performed. Results: Out of 67 patients, 40 (59.7%) experienced irAEs, 7(10.4%) experienced severe adverse events (Grade ≥3). Among the immune‑profile biomarkers analyzed, only interleukin‑10 (IL-10) was associated with the risk of toxicity. High baseline interleukin‑10 serum level (OR=5.318,95%CI 1.174-24.081, P=0.030) was significant and independent risk factors for immune-related adverse events. Also, for dynamic analysis, upregulation of IL-10 after one-cycle of ICIs treatment was positively related with occurrence of irAEs (OR=5.712, 95% CI 1.088-29.993, P=0.039). When take pneumonitis, the most common irAEs, into analysis, only baseline high-expression IL-10 was associated with the incidence of pneumonitis. (OR=9.969,95%CI 1.144-86.843, P=0.037).